Dual Supramolecular Nanoparticle Vectors Enable CRISPR/Cas9‐Mediated Knockin of Retinoschisin 1 Gene—A Potential Nonviral Therapeutic Solution for X‐Linked Juvenile Retinoschisis. Issue 10 (16th April 2020) - Chou, Shih‐Jie; Yang, Peng; Ban, Qian; Yang, Yi‐Ping; Wang, Mong‐Lien; Chien, Chian‐Shiu; Chen, Shih‐Jen; Sun, Na; Zhu, Yazhen; Liu, Hongtao; Hui, Wenqiao; Lin, Tai‐Chi; et al.
Abstract: The homology‐independent targeted integration (HITI) strategy enables effective CRISPR/Cas9‐mediated knockin of therapeutic genes in nondividing cells in vivo, promising general therapeutic solutions for treating genetic diseases like X‐linked juvenile retinoschisis. Herein, supramolecular nanoparticle (SMNP) vectors are used for codelivery of two DNA plasmids—CRISPR‐Cas9 genome‐editing system and a therapeutic gene, Retinoschisin 1 (RS1)—enabling clustered regularly interspaced short palindromic repeats (CRISPR)‐associated protein 9 (CRISPR/Cas9) knockin of the RS1 gene with HITI. Through small‐scale combinatorial screenings, two SMNP vectors, with Cas9 and single guide RNA (sgRNA)‐plasmid in one and Donor‐RS1 and green fluorescent protein (GFP)‐plasmid in the other, with optimal delivery performances are identified. These SMNP vectors are then employed for CRISPR/Cas9 knockin of RS1/GFP genes into the mouse Rosa26 safe‐harbor site in vitro and in vivo. The in vivo study involves intravitreally injecting the two SMNP vectors into the mouse eyes, followed by repeated ocular imaging by fundus camera and optical coherence tomography, and pathological and molecular analyses of the harvested retina tissues. Mice ocular organs retain their anatomical integrity, a single‐copy 3.0‐kb RS1/GFP gene is precisely integrated into the Rosa26 site in the retinas, and the integrated RS1/GFP gene is expressed in the retinas, demonstrating CRISPR/Cas9 knockin of RS1/GFP gene. Abstract : Two supramolecular nanoparticle (SMNP) vectors codeliver two DNA plasmids—a CRISPR‐Cas9 construct and a therapeutic gene, RS1. Both SMNP vectors are intravitreally injected into the eyes of mice to enable CRISPR/Cas9 knockin of the RS1 gene using the homology‐independent targeted integration (HITI) strategy, to test a potential nonviral therapeutic solution for X‐linked juvenile retinoschisis (XLRS).